UNCLOS Gaps and the Blue Economy: Integrating International Maritime Law and Fiqh al-Bī’ah for Sustainable Ocean Governance - Ahmad Iffan; Hendriko Arizal; Arif Roihan; Muhammad Faiz Algifari (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
Existing blue economy frameworks and international maritime governance continue to face limitations in addressing contemporary marine sustainability challenges, particularly biodiversity loss, deep-sea mining, unequal benefit-sharing, and weak implementation mechanisms. This study examines how international maritime law, particularly the 1982 United Nations Convention on the Law of the Sea (UNCLOS), can support the blue economy and SDG 14, while also analyzing the ethical contribution of Fiqh al-Bī’ah (Islamic environmental jurisprudence) to sustainable ocean governance. Using a normative juridical approach, this research analyzes international legal instruments, policy documents, and scholarly literature related to maritime governance, the blue economy, SDG 14, and Islamic environmental ethics. The findings show that although UNCLOS provides an important legal foundation for marine environmental protection, sustainable resource use, benefit-sharing, and international cooperation, several normative and implementation gaps remain, especially in relation to biodiversity beyond national jurisdiction and deep-sea mining. The study further finds that Fiqh al-Bī’ah principles, including khilāfah, mīzān, amānah, and lā ḍarar wa lā ḍirār, can complement international maritime law by strengthening ethical responsibility, ecological balance, and intergenerational justice. This integration offers an interdisciplinary framework for sustainable maritime governance, particularly for maritime and Muslim-majority states such as Indonesia.